2021
DOI: 10.3390/v13122465
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleocapsid of Paramyxoviruses: Structure and Function of an Encapsidated Template

Abstract: Viruses of the Paramyxoviridae family share a common and complex molecular machinery for transcribing and replicating their genomes. Their non-segmented, negative-strand RNA genome is encased in a tight homopolymer of viral nucleoproteins (N). This ribonucleoprotein complex, termed a nucleocapsid, is the template of the viral polymerase complex made of the large protein (L) and its co-factor, the phosphoprotein (P). This review summarizes the current knowledge on several aspects of paramyxovirus transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 220 publications
(422 reference statements)
0
11
0
Order By: Relevance
“…Similarly to other Mononegavirales 20,21 , the N- and C-terminal extensions of RSV N, termed NTD-arm (residues 1-36) and CTD-arm (residues 360-391) (Figure 1h), interact with the laterally adjacent N protomers thereby stabilising their oligomeric assembly on the RNA strand by subdomain swapping (Figure 2a). The visible part of the CTD-arm of N i lies on top of the CTD of N i+1 implying that in a helical NC it should be situated in between consecutive turns 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to other Mononegavirales 20,21 , the N- and C-terminal extensions of RSV N, termed NTD-arm (residues 1-36) and CTD-arm (residues 360-391) (Figure 1h), interact with the laterally adjacent N protomers thereby stabilising their oligomeric assembly on the RNA strand by subdomain swapping (Figure 2a). The visible part of the CTD-arm of N i lies on top of the CTD of N i+1 implying that in a helical NC it should be situated in between consecutive turns 4 .…”
Section: Resultsmentioning
confidence: 99%
“…All Mononegavirales NCs are left-handed helices, with the CTDs and the 3'-end of the RNA oriented towards the pointed end of the filaments and the NTDs and the 5'-end towards the barbed ends 20 . The paramyxoviral clam-shaped assemblies were proposed to seed the growth of the double-headed helices from the 5' to the 3' end, protect the 5' end from nucleases 10 and support encapsidation of several NCs per virion 24 , also documented for RSV 19,25 .…”
Section: Molecular Determinants Of the Longitudinal Ntd-ntd Interactionmentioning
confidence: 99%
“…Other RNP-like particle structures have been solved in recent years by cryoEM for other paramyxoviruses (e.g., a cetacean morbillivirus or Sendai virus) [ 44 , 45 ]. Additional reviews specific to the nucleocapsid structure of paramyxoviruses can be found in [ 37 , 46 , 47 ].…”
Section: Structure Of the Nucleocapsid Of -Ssrnavmentioning
confidence: 99%
“…For example, the HeV N protein α5-loop region contains two amino acid substitutions compared with the NiV N protein; L108V and E137D, both of which are solvent exposed [32]. Whether there is a functional relevance to these substitutions is unknown, however in the context of a helical nucleocapsid the α5-loop region is the main solvent exposed section of the N protomer and may be important for interactions with the RdRp complex during transcription and replication, or could potentially interface in-phase with the M protein lattice during virion assembly, as proposed for other paramyxoviruses [17][18][19]. Furthermore, the α5-loop region has also been identified as the main interface in intercalating interactions in the HeV N protein assembly (Figure 5), as well as in clamshell formation in NDV, NiV, and SeV nucleocapsid-like filaments (NLFs) [32,37,38].…”
Section: Comparison With Other Paramyxoviral N Protein Assembliesmentioning
confidence: 99%
“…The nucleocapsid associates with the viral RNA dependent RNA polymerase (RdRp) comprising the large (L) and phospho (P) proteins to form the holonucleocapsid. The N-RNA interaction is critical for virus multiplication as genomic RNA is only recognised by the RdRp as a template for mRNA transcription and genome replication when in the context of the assembled nucleocapsid (reviewed in [17]), and incorporation of genomic RNA into new virions depends on interactions between N protein within the nucleocapsid and the viral matrix (M) protein [1719].…”
Section: Introductionmentioning
confidence: 99%